Assessment of hydrological inspection using development low-cost boat application in University Sultan Zainal Abidin (UniSza) Lake, Terengganu, Malaysia - Kamarudin, Mohd Khairul Amri; Mustapha, Mohammad Faezul Hakim; Abd Wahab, Noorjima; Md. Saad, Muhammad Hafiz; Toriman, Mohd Ekhwan; Mohd Hamzah, Firdaus; Abu Samah, Mohd Armi; Abu Hassan, Mohd Syaiful Nizam; Md Bati, Siti Nor Aisyah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Unmanned vehicles may provide less time consume and cost-effective methods of gathering hydrographic survey data compared to traditional, manned survey vessels. A remote-controlled Unmanned Surface Vehicle (USV) was outfitted with range finder, depth transducer, and velocity current meter for the purpose of conducting a hydro survey. The purpose of study to describes a project for the development of Unmanned Survey Vessel (USV) platform useful for hydrological survey. The control unit includes a motor control system, communication equipment, and a simple radio control system installed to enables an operator to remotely control the boat. The motor radio control system, the measurement equipment (sonar depth, current meter, range finder) used in data collecting activities. The result showed the validation values of Hydro Survey Boat Version 1 and Hydro Survey Boat Version 2, the estimated validation of river discharge (Q) recorded 0.0373 m3/s. The significant differences of Q between Hydro Survey Boat Version 1 as 0.0853 m3/s (56.3%) and Hydro Survey Boat Version 2 as 0.042 m3/s (11.2%) which is the Hydro Survey Boat Version 2 recorded more accurate readings compared Hydro Survey Boat Version 1. There are several advantages of this project which is reducing cost, improve efficiency, and reduce risk during hydrology survey. The development survey boat USV is innovation technology and it will improved the hydrological method.